Rancang Bangun E-Learning Penggolongan Jenis Napza Menggunakan Metode Waterfall - Devi Wulandari; Pasipikus Yosua Agun; Ferian Fauzi Abdulloh; Abdul Muin (Intechno Journal : Information Technology Journal, 2024)
In the context of Sleman Regency, Indonesia, the rate of drug abuse is increasing due to insufficient dissemination of information about the types of drugs and the negative impacts resulting from drug abuse. One of the contributing factors is the lack of socialization among the community, leading to their limited knowledge about the types of drugs and the dangers of improper use or using medication without a doctor's prescription. The approach applied to combat this problem is a systematic method that involves planning the system, analysis, design, implementation, testing, and maintenance. These steps must be carried out in a sequential manner. The system itself will be developed using programming languages such as PHP, JavaScript, and MySQL server for data processing